Two classes of bacterial IMPDHs according to their quaternary structures and catalytic properties. - Thomas Alexandre; Bertrand Raynal; Hélène Munier-Lehmann (PLoS ONE)
Inosine-5'-monophosphate dehydrogenase (IMPDH) occupies a key position in purine nucleotide metabolism. In this study, we have performed the biochemical and physico-chemical characterization of eight bacterial IMPDHs, among which six were totally unexplored. This study led to a classification of bacterial IMPDHs according to the regulation of their catalytic properties and their quaternary structures. Class I IMPDHs are cooperative enzymes for IMP, which are activated by MgATP and are octameric in all tested conditions. On the other hand, class II IMPDHs behave as Michaelis-Menten enzymes for both substrates and are tetramers in their apo state or in the presence of IMP, which are shifted to octamers in the presence of NAD or MgATP. Our work provides new insights into the IMPDH functional regulation and a model for the quaternary structure modulation is proposed.